Alih Kode dan Campur Kode dalam Film Turah Karya Wicaksono Wisnu Legowo : Teori Sosiolinguistik - Adinda Abhi Riskita; Udjang Pairin (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Code-switching and code-mixing are common in various types of media, such as movies, TV shows, books, and articles. This research uses a descriptive qualitative approach to examine and describe data on code-switching and code-mixing. By using this approach, the researcher can provide a detailed description of how this linguistic phenomenon occurs in the context of the movie. The researcher collected data by watching and listening to the movie Turah and taking notes. This allowed the researcher to record the form of code-switching and code-mixing. The purpose of this study is to describe how the form of code-switching and code-mixing, as well as the factors that can cause the occurrence of code-switching and code-mixing